Implementasi Penggunaan Istilah Bahasa Arab Pada Masa Pandemi Dalam Linguistik Historis - Fuadhi, Muhammad Iqbal; Muflihah, Muflihah; Muttaqiyyah, Almar’atul; Munazzalurrohmi, M.; Herman, Herman (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This research discusses how language continues to evolve along with the development of an era, with terms and vocabulary that did not exist before becoming present. When the Covid-19 pandemic spread worldwide, language underwent a transformation, leading to the emergence of new vocabulary and terms that were previously unfamiliar but became familiar to the public. Because of the continuous communication among humans. Historical linguistics serves as a comparative tool in the context of the historical development of languages, including their linguistic elements. Historical linguistics serves as an analytical tool to address the historical emergence of a language and investigate its relationship with other languages in terms of kinship, examining whether there are similarities within the language 's linguistic context. This research uses a qualitative type of study with a descriptive approach. The research results indicate that the use of Arabic terms during the Covid-19 pandemic corresponds with the conditions that have occurred over time, starting from the time of the Prophet Muhammad, who used the term Tha'un to describe the plague that struck then, followed by the Spanish flu in the 19th century, which was referred to as the Spanish flu pandemic, and in the 21st century, the Covid-19 pandemic, also known as the corona virus.